Enhancers of cancer stem cells and epithelial–mesenchymal transition: Lin28, MUC1, and lipocalin-2 as a new prognostic axis in classical invasive lobular carcinoma of the breast - Mohamed Alabiad; Raja Aljafil; Amany Shalaby; Ahmed M. Yehia; Mohammed Alorini; Basma Hamed Ibrahim (Polish Journal of Pathology)
Breast carcinoma is one of the most common causes of cancer-related mortality among women worldwide. The primary objective of the present study was to evaluate the expression of the epithelial-mesenchymal transition (EMT)-related markers Lin28, MUC1, and lipocalin-2 in invasive lobular carcinoma (ILC) and to investigate their correlation with clinicopathological characteristics and patient survival. This prospective cohort study included 120 classic ILC cases investigated for immunohistochemical expressions of Lin28, MUC1, and lipocalin-2 and followed them for five years or until death. The expression of markers in all tissue samples was assessed, analysed, and correlated with clinical-pathological parameters and outcomes. Lin28, MUC1, and lipocalin-2 were positively expressed in 55%, 75%, and 45%, respectively. The high expression of Lin28 and MUC1 and low lipocalin-2 were associated with poor clinicopathological characteristics and unfavourable overall survival. Lin28 and MUC1 were highly expressed in ILC and were associated with lower survival rates, poor outcomes, and a pessimistic prognosis in patients with ILC, while lipocalin-2 expression was associated with a positive outcome where its down-regulation was related to a poor prognosis in patients with ILC. Furthermore, we concluded that Lin28, MUC1, and lipocalin-2 could influence cancer behaviours, including proliferation, invasion, and migration, by regulating the EMT process and CSC criteria in ILC cells, making them potentially advantageous indicators and targeted treatments. Our research may have significant implications for understanding the pathophysiology and prognosis of ILC, which could help select treatment targets.